Incidence of vocabulary mastery in the reading comprehension of Chilean students with intellectual disabilities - Gallego Ortega, José Luis; Figueroa Sepúlveda, Susana (Revista de Investigación en Logopedia, 2020)
Reading has traditionally attracted the interest of professionals and researchers. However, studies that have explored reading comprehension skills in Spanish-speaking subjects with intellectual disabilities (ID), whose etiology is unknown or diverse are testimonial and research that analyzes the influence of the vocabulary mastery on the reading performance of these school children is non-existent. In this sense, a novel study was set to analyze the relation between vocabulary and reading comprehension in an ID population, based on a descriptive and correlational analysis. A sample of 22 Chilean elementary school children with ID from three urban schools of different administration types participated in the study. Results showed that only in the group of boys there were significant correlations between both variables. These results and their importance for the design of strategies that will allow this group to have a better reading performance are discussed.